2019
DOI: 10.3390/cells8050422
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Localization of Branchial AQP1 and AQP3 in Japanese Medaka (Oryzias latipes)

Abstract: Aquaporins (AQPs) facilitate transmembrane water and solute transport, and in addition to contributing to transepithelial water transport, they safeguard cell volume homeostasis. This study examined the expression and localization of AQP1 and AQP3 in the gills of Japanese medaka (Oryzias latipes) in response to osmotic challenges and osmoregulatory hormones, cortisol, and prolactin (PRL). AQP3 mRNA was inversely regulated in response to salinity with high levels in ion-poor water (IPW), intermediate levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…8 B). It has been demonstrated that the gill tissue improves active ion absorption capacity and resists ion loss by increasing the expression levels of NHE3 , CLC-2 , and AE2, when fishes migrate from high-salt environment to freshwater [ 15 , 47 49 ]. Numerous previous studies have shown that NKA-α expression decreases when water temperature increases [ 22 , 50 , 51 ], this was substantiated by the change results of heat stress at 28℃ and 24℃ when compared to 20℃ in our study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 B). It has been demonstrated that the gill tissue improves active ion absorption capacity and resists ion loss by increasing the expression levels of NHE3 , CLC-2 , and AE2, when fishes migrate from high-salt environment to freshwater [ 15 , 47 49 ]. Numerous previous studies have shown that NKA-α expression decreases when water temperature increases [ 22 , 50 , 51 ], this was substantiated by the change results of heat stress at 28℃ and 24℃ when compared to 20℃ in our study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to lead and other heavy metals induces osmoregulatory dysfunctions that are recognized as the main toxicity mechanisms of these pollutants in seawater and freshwater fish [ 20 , 29 , 60 , 61 ]. In basal conditions, Na + /K + -ATPase and aquaporin-3 (AQP3) are widely expressed within this key osmoregulatory organ and localize in the basolateral membrane of chloride cells (CCs), where they mediate the movements of water and selected ions between intracellular and extracellular fluids [ 42 , 43 ]. CCs are often a target of heavy metals’ toxicity [ 62 ], and in situations that prevent their normal function, the gills might promote their differentiation to increase ions uptake [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to evaluate the functional disorders under experimental conditions, we used a real-time PCR (RT-PCR) to detect and quantify key enzymes correlated to specific Pb toxicity pathways in zebrafish gills in a second step. Na + /K + -ATPase and aquaporin-3 (AQP3) are expressed within key osmoregulatory tissues where they mediate the active transmembrane movement of water and selected ions between intracellular and extracellular fluids [ 42 , 43 ] and are widely recognized as valuable biomarkers in xenobiotics-induced osmotic stress [ 24 , 26 , 29 , 44 , 45 ]. In fish, protective pathways are activated to regulate heavy metal ions and prevent tissue damage [ 46 , 47 ], including metallothioneins (MTs) induction.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies suggest that aqp3 and ncc2a are also implicated in gill functions since SW adapted fish show significant levels of the transcripts (Blondeau-Bidet et al, 2019a;Breves et al, 2020;Giffard-Mena et al, 2007;Jung et al, 2012;Moorman et al, 2015;Tipsmark et al, 2010). Aqp3 immunoreactivity appears quantitatively similar whatever the salinity in medaka (Ellis et al, 2019) and protein abundance does not change significantly in killifish (Jung et al, 2012). Ncc2 protein was also quantified in SW-acclimated mummichogs using western blot approach (Breves et al, 2020).…”
Section: Biomarkers Related To Ions and Water Homeostasismentioning
confidence: 99%